HUBUNGAN PEMAHAMAN HADIS MENGHARGAI WAKTU TERHADAP DISIPLIN WAKTU - Pausi Pausi; Ahmad Faqih Hasyim; Amin Iskandar (IAIN Syekh Nurjati Cirebon, 2023)
Discipline is very important for any serious learner or learner of knowledge. Based on observations, implementing a disciplined lifestyle can be seen from the daily activities of the students, starting from the discipline of getting up in the morning, praying at the mosque on time, teaching and learning activities, and going to school. This study aims to determine whether the level of understanding of students affects their disciplinary actions at Al-Urwatul Wutsqo Islamic Boarding School. The research design is a social problem study based on hypothesis testing using a quantitative methodology. The population in this study were 11th grade Al- Urwatul Wutsqo Islamic Boarding School students who majored in MA as many as 30 people. Data collection techniques were carried out through interviews and questionnaires. Data analysis in this study used bivariate analysis and correlation analysis. The results showed that the understanding and knowledge of Al-urwatul Wutsqo Islamic Boarding School students on hadith respecting time is included in the moderate category which is at intervals (4-6) with a total of 13 people (43.3%). Discipline character at school is included in the medium and high categories. While the character of discipline when going to the mosque is included in the high category with a total percentage of 70% (27 people). Based on data analysis, it was found that there was a significant relationship between the understanding of hadith respecting time and the time discipline of students at the Al-Urwatul Wutsqo Indramayu Islamic Boarding School.